Examining Psychological Quality Requirements and Training for English Interpreters in Sports Psychology - Yanran Sun (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to study the psychological quality requirements and training of English interpreters in sports psychology. This paper first introduces the main reasons of psychological stress and puts forward the influence of psychological quality on the effect of interpretation: inverted U hypothesis. Through the analysis, we can see that the interpretation process is a process full of passion, wits and courage. Behind the shadow of the language is also accompanied by a psychological contest. At present, the interpretation courses offered in domestic universities mainly focus on interpretation training under different situations and technical training in the process of instantaneous conversion of two languages, and practice has proved that psychological quality training is also necessary for interpreters. When students go out of the classroom and step into the society, the good psychological quality established in the process of interpretation training can benefit them for life. Interpreting, like sports competitions, is conducted on-site. As interpreters, like athletes, there is an optimal level of arousal psychologically. When the level of psychological tension reaches this optimal arousal point, the interpreting effect will reach its best level. As an on-site translator, one also needs to possess some special psychological characteristics. In our interpretation class teaching, students should be consciously trained in psychological qualities.